Thermochemical Properties of 2,4,6-Trinitro-1,3,5-triazine - HOSSEIN KESHAVARZ, MOHAMMAD; RANAEE SYADAT, OMID (Asian Journal of Chemistry, 2010)
Theoretical studies of explosives continue to seek new compounds that can have higher performance and better thermochemical properties than RDX (cyclotrimethylenetrini-tramine) and HMX (cyclotetramethylenetetranitramine). 2,4,6-Trinitro-1,3,5-triazine is one of the interesting explosive with high performance as compared to HMX and RDX. The purpose of this work is to present computed or calculated thermochemical properties of 2,4,6-trinitro-1,3,5-triazine such as detonation temperature, adiabatic exponent, impact sensitivity, heat of detonation by using empirical and semiempirical methods.